MAKNA KODRAT ALAM DAN KODRAT ZAMAN DALAM PENERAPAN NILAI-NILAI BUDAYA RELIGI: STUDI FENOMENOLOGI DI SD IT AHMAD DAHLAN KOTA JAMBI - Abdul Razaq; Arsita Arsita; Ayu Mutoharoh; Depa Aprilia Saputri; Devi Ariska (Jurnal Tunas Pendidikan, 2025)
The concept of nature and time are integrated into the application of religious cultural values to support the formation of religious, environmentally conscious, and adaptive students' characters. This study aims to explore more deeply the understanding of the concept of nature and time in the implementation of religious cultural values at SD IT Ahmad Dahlan. The research approach used is a qualitative phenomenological approach. Data collection techniques used are observation, interviews, and documentation. The results of this study are the application of religious cultural values based on the concept of nature and time produce students who have character, are adaptive to technology, and care about the environment.